2017
DOI: 10.1007/s00705-017-3294-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of hepatitis A virus circulating in Egypt

Abstract: Hepatitis A virus (HAV) still poses a considerable problem worldwide. In the current study, hepatitis A virus was recovered from wastewater samples collected from three wastewater treatment plants over one year. Using RT-PCR, HAV was detected in 43 out of 68 samples (63.2%) representing both inlet and outlet. Eleven positive samples were subjected to sequencing targeting the VP1-2A junction region. Phylogenetic analysis revealed that all samples belonged to subgenotype IB with few substitutions at the amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
3
16
1
1
Order By: Relevance
“…Previous studies were confirmed our data that genotype IB is the predominant genotype circulating in Egypt and North Africa (Robertson et al, 1992;Costa-Mattioli, 2007 andHamza et al, 2017). Furthermore, Hamza et al (2017) demonstrated the VP1/2A nucleotide sequences of all Egyptian isolates were 99.7% identical to each other and 96.4 to 97.6% identical to strains of the IB genotype.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Previous studies were confirmed our data that genotype IB is the predominant genotype circulating in Egypt and North Africa (Robertson et al, 1992;Costa-Mattioli, 2007 andHamza et al, 2017). Furthermore, Hamza et al (2017) demonstrated the VP1/2A nucleotide sequences of all Egyptian isolates were 99.7% identical to each other and 96.4 to 97.6% identical to strains of the IB genotype.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies were conducted to evaluate HAV circulation in the Egyptian environment (Kamel et al, 2011 andHamza et al, 2017). Molecular characterization of HAV is important for understanding its circulation pattern and evolutionary relationships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Formerly known as infectious hepatitis, hepatitis A is caused by the hepatitis A virus [1][2][3]. Hepatitis A virus (HAV) belongs to the genus Hepatovirus of the family of Picornaviridae [4][5][6].…”
Section: Introductionmentioning
confidence: 99%